2009
DOI: 10.1007/s11999-009-0830-x
|View full text |Cite
|
Sign up to set email alerts
|

High Cup Angle and Microseparation Increase the Wear of Hip Surface Replacements

Abstract: High wear rates and high patient ion levels have been associated with high (> 55 degrees) cup inclination angles for metal-on-metal surface replacements. Wear rates and patterns have been simulated for ceramic-on-ceramic bearings by applying microseparation to replicate head offset deficiency. We tested 39-mm metal-on-metal surface replacements (n = 5) in a hip simulator with (A) an increased cup inclination angle of 60 degrees and (B) an increased cup inclination angle and microseparation over 2 million cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
176
2
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 178 publications
(186 citation statements)
references
References 22 publications
7
176
2
1
Order By: Relevance
“…This is consistent with the results of our multivariate model, showing no significant association between radiographic signs of impingement and high CoS or CrS levels after adjusting for contact patch to rim distance and activity level. These results are in agreement with those of Leslie et al [18] who showed increased wear rates in vitro in metal-on-metal bearings combining microseparation (a condition that could result from impingement) with outof-range cup positioning.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the results of our multivariate model, showing no significant association between radiographic signs of impingement and high CoS or CrS levels after adjusting for contact patch to rim distance and activity level. These results are in agreement with those of Leslie et al [18] who showed increased wear rates in vitro in metal-on-metal bearings combining microseparation (a condition that could result from impingement) with outof-range cup positioning.…”
Section: Discussionsupporting
confidence: 93%
“…All measurements used in the study were completed by a single reader (MC). Acceptable angle ranges were set at 30°to 45°for abduction and 5°to 25°for version based on surgeon consensus and standards from previous studies [12,25,26,54].…”
Section: Methodsmentioning
confidence: 99%
“…Increased wear debris from the bearing surface can lead to osteolysis and aseptic loosening of the joint [6,16,21]. This increased wear can be seen in both hard-on-soft and hard-on-hard bearing surfaces [11,14,25,38]. Importantly, recent reports on metal-on-metal bearings describe an increased risk of tissue reactions around these bearings related to metal debris from edge loading of cups [29,41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory simulator studies have shown that microseparation produces stripe wear at the bearing surfaces (Figure 1) and dramatically elevated wear rates20 in MoM bearings. Simulator tests have also been carried out in an attempt to investigate the effects of head sizes and cup inclination on elevated wear20, 21 under microseparation conditions; these tests have been generally focused on a fixed translation level of 0.5 mm. A full range of parametric studies which can incorporate a wide range of variations in microseparation displacement, cup orientation and cup rim radius are currently not available with simulator tests.…”
Section: Introductionmentioning
confidence: 99%